2019
DOI: 10.1038/s41598-019-45474-8
|View full text |Cite
|
Sign up to set email alerts
|

Radiation emission in laser-wakefields driven by structured laser pulses with orbital angular momentum

Abstract: High-intensity X-ray sources are invaluable tools, enabling experiments at the forefront of our understanding of materials science, chemistry, biology, and physics. Laser-plasma electron accelerators are sources of high-intensity X-rays, as electrons accelerated in wakefields emit short-wavelength radiation due to betatron oscillations. While applications such as phasecontrast imaging with these betatron sources have already been demonstrated, others would require higher photon number and would benefit from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…It involves Fourier transforming the input signal and adding a phase, in accordance with the dispersion relation of the waves and distance between input and output planes, to determine the output signal. Mathematically, it is described in Equation (8).…”
Section: Methods Used For Numerical Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It involves Fourier transforming the input signal and adding a phase, in accordance with the dispersion relation of the waves and distance between input and output planes, to determine the output signal. Mathematically, it is described in Equation (8).…”
Section: Methods Used For Numerical Simulationsmentioning
confidence: 99%
“…For implementation of the Debye-Wolf integral, we used Equations (11)- (14) from Reference [30], with wavefront aberration determined according to Equation (9) and the complex amplitude of the beam, denoted by V lens , determined using Equations (8) and (10). The complex amplitude of the beam in the output plane, in the point R, is proportional to the complex amplitude of the plane-wave with direction given by the ray vector of the ray that passes through R. Since there is a one-to-one correspondence between the position in the transversal plane, after the focusing element, and the transversal projection of ray vector t, we can index the complex amplitude depending on t as shown in Equation 11.…”
Section: Methods Used For Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies suggest methods for enhancing betatron radiation emission, mostly based on the increase of the betatron oscillation amplitude. This can be achieved by an axial magnetic field, either self-generated or external 17 , 18 ; by a delayed modulation laser pulse 19 ; by the interaction of the electron beam with a high intensity optical lattice formed by the superposition of two transverse laser pulses 20 ; by using structured laser pulses 21 ; or by the interaction of electrons with the tail of the plasma wave drive pulse 22 25 .…”
Section: Introductionmentioning
confidence: 99%
“…It has also been theoretically demonstrated that the angular momentum of light can be transferred to a plasma wakefield using a spatiotemporally shaped beam [17]. There are proposals to use intense OAM laser pulses for creating a suitable wake for electron/positron acceleration [18,19,20], ion acceleration [21], radiation emission [22], and magnetic field generation [23,24]. Most of these applications require vortex beams with relativistic intensity.…”
mentioning
confidence: 99%